O olhar de assistentes sociais da educação sobre a prática profissional: estudo em uma perspectiva fenomenológica no Distrito DAGUA em Belém do Pará - PANTOJA, Gleidson Alves (Universidade Federal do Pará, 2015)
The research objectives were to assess the professional practice / social worker, the area of education, the Administrative District of Guama (DAGUA) in Belém-Pará; the degree of influence of lifestyles that make experiences present in the social development of the individual case, and particularly in the work of these social workers process. Left of the assumptions that: the way of life influences the professional practice / social worker; the practice of social work is being rethought in everyday life; the social worker has a defined understanding of the theory you use in everyday practice; works published in Brazil currently do not meet the theoretical-methodological and operative technical dimensions of Social Service. Employs various techniques for the implementation of research and dialogue with currents of thought that influence social work since its inception. Appropriates the phenomenology for the dialectical interpretation of the results and also the Marxist theory as support reading of the reality. The existential-phenomenological method enabled to grasp the concrete / real in the reports of the interviews, which was evident in day to day issues of School Social Work, as the scarcity of professionals, bad structural conditions for the realization of professional intervention, the issue of various forms of violence, poor training, the need for greater openness to the plurality of ideas in theoretical and methodological conduct of professional practice.